A Psychotheological Approach to the Development of Children's Faith and Personality in Christian Religious Education - Rumiyati Rumiyati; Meniati Hia (Jurnal Didaskalia, 2026)
This study explores the integration of developmental psychology and Christian theology in understanding the formation of children's faith and personality through Christian Religious Education (CRE). A psychotheological approach is employed to bridge the scientific understanding of human psychological and spiritual development with the dimension of faith derived from divine revelation. Employing a qualitative library research design, this study examines James Fowler's theory of faith development, Erik Erikson's psychosocial theory, and the biblical perspective on children's spiritual growth. The analysis reveals that the development of faith and personality in children cannot be separated from their dynamic relationship with God, the family as the primary institution of faith formation, and the faith community as a formative environment. Psychotheologically-based CRE equips teachers to become facilitators of holistic faith development, addressing the cognitive dimension through doctrinal understanding, the affective dimension through spiritual experience, and the moral dimension through Christian ethics, thereby systematically forming Christlike character within the child. This study also outlines practical implications for curriculum development and teaching methodologies in CRE that are responsive to children's developmental stages and grounded in strong theological principles.